Effects of feeding corn silage, pelleted, ensiled, or pelleted and ensiled alfalfa on growth and carcass characteristics of lamb - Fluharty, F. L. (2017)
Two experiments were conducted to evaluate the effects of corn silage (CS) and alfalfa (pelleted (AP), haylage (AH), or combination (APH)) on lamb growth and carcass characteristics. The objective of Experiment 1 (Exp. 1) was to compare AH to CS in lamb feedlot diets on lamb growth and carcass characteristics. Eighty lambs were used in a 56 day experiment with a randomized complete block design. The objective of Experiment 2 (Exp. 2) was to determine the effects of alfalfa form, AP, AH or AHP, on animal performance and carcass characteristics. Seventy two lambs were used in an 82 day experiment with a randomized complete block design. In Exp. 1, lambs offered AH consumed 23.5% more feed on a daily basis than lambs offered CS. However, lambs fed CS gained weight 21.3% faster than lambs fed AH (259 versus 213 g/day, respectively). Additionally, lambs fed CS were 50.4% more efficient in converting feed to gain compared with lambs offered AH (0.173 versus 0.115 kg gain/kg feed, respectively). In Exp. 2, AP resulted in a greater dry matter intake (DMI) and average daily gain (ADG), and fewer days on feed than with AH. The combination of pellets + haylage resulted in a greater DMI, ADG, and fewer days on feed compared to AH alone. Therefore, there was an inverse relationship between both forage particle size and diet moisture content with DMI. There was no difference in daily efficiency of gain due to the form of alfalfa. Average daily gain, days on feed, and DMI are economically important criteria that differ due to the form of alfalfa even when feed efficiencies are similar.